2010
DOI: 10.1016/j.jvs.2010.03.068
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of gender-related outcome differences after carotid endarterectomy

Abstract: Higher embolic potential in women and relatively stable female plaque morphology are the best-described factors influencing the difference in outcomes between men and women. However, the overall evidence for outcome differences by gender-specific characteristics in the literature is limited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
25
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 77 publications
3
25
1
1
Order By: Relevance
“…Greater diameters among men were expected and confirmed 23,24 . The length of stay in the hospital was shorter in men compared to women 12 .…”
Section: Discussionsupporting
confidence: 60%
“…Greater diameters among men were expected and confirmed 23,24 . The length of stay in the hospital was shorter in men compared to women 12 .…”
Section: Discussionsupporting
confidence: 60%
“…[1][2][3][4] The underlying pathophysiologic mechanisms that explain these sexspecific differences are poorly understood. 5 The stability of the atherosclerotic plaque may be one of the factors that explain these findings. In line with previous observations showing a more unstable plaque phenotype in men, 6 we observed that PH in the atherosclerotic plaque is more prevalent in men with carotid artery stenosis.…”
Section: Discussionmentioning
confidence: 99%
“…Subgroup analyses from randomized trials have indicated that the risk reduction of stroke after carotid endarterectomy (CEA) is less evident in women than in men. [1][2][3][4][5] One of the possible factors contributing to this sex-associated difference is carotid plaque phenotype, which is significantly more stable in women, especially in asymptomatic patients. 6 Plaque hemorrhage (PH) may lead to accelerated progression of atherosclerotic disease.…”
mentioning
confidence: 99%
“…[19][20][21][22][23][24][25][26][27][28][29] However, the overall evidence for outcome differences by gender-specific characteristics in the literature is limited. 30 Mantese et al found that sex did not modify the treatment effect. 31 Some authors emphasize that female sex alone is not an adjunctive risk factor for poor outcome after CEA in comparison to male patients, however subgroups of female patients at ahigher surgical risk can be distinguished -with contralateral occlusion or diabetes.…”
Section: Discussionmentioning
confidence: 98%